The autoimmune storm: A mother’s battle in the womb - Bhutada, Akshay; Das, Madhumita Priyadarshini; Das, Marami; Goswami, Munindra (Indian Journal of Case Reports, 2025)
Myasthenia gravis (MG) is an autoimmune disorder affecting the neuromuscular junction, often diagnosed in women of reproductive age. Pregnancy can exacerbate MG symptoms, and management becomes complex in the presence of coexisting infections or autoimmune overlap syndromes. We report a 36-year-old pregnant woman who presented with generalized MG, confirmed by a positive acetylcholine receptor antibody and decremental response on repetitive nerve stimulation. Initial therapy included pyridostigmine, intravenous immunoglobulin (IVIg), and corticosteroids. She was found to be hepatitis B surface antigen (HBsAg) positive with a high hepatitis B virus DNA load, for which entecavir was initiated. At 5 months’ gestation, she experienced a relapse with raised inflammatory markers, strong Ro-52 positivity, and perinuclear antineutrophil cytoplasmic antibody seropositivity. She was managed conservatively with IVIg and steroids during pregnancy. Following an uneventful delivery, she experienced a postpartum crisis, managed successfully with IVIg and cyclophosphamide. Azathioprine was added for long-term maintenance. She has remained in remission for over a year. This case highlights the rare combination of MG, chronic hepatitis B, and autoimmune overlap syndrome during pregnancy. With a multidisciplinary, individualized treatment strategy, including antiviral prophylaxis and immunotherapy, excellent maternal and fetal outcomes were achieved.